The Effectiveness of Sheltered Instruction Observation Protocol (SIOP) Model of Developing Mathematical Achievement in Preparatory Year Female Students at Al-Imam Mohammad Ibn Saud Islamic University - Alnusayan, Iman Sulaiman; Al-Salouli, Misfer Saud (Journal of Educational and Psychological Sciences, 2020)
The aim of this research was to investigate the effectiveness of the sheltered instruction observation protocol (SIOP) model in teaching mathematics in English language for the preparatory year in improving the level of mathematical achievement. To achieve the aims of the research, the mixed design of the concurrent type was used, in which quantitative and qualitative data were collected simultaneously. The study was applied to a sample of (167) students in the preparatory year of Imam Muhammad bin Saud Islamic University for the first applied track. They were divided into two experimental groups that were taught Mathematics using the sheltered instruction observation protocol (SIOP) model and two control groups that were taught Mathematics using the usual standard method. The groups were subjected to an achievement test, and a sample was chosen according to the level of the achievement test for individual interviews.The results of the research showed that there is a statistically significant difference at the level of (α ≤ 0.05) between the average score of the female students in the control groups who were taught according to the traditional method, and those in the experimental groups who were taught according to the sheltered instruction observation protocol (SIOP) model in the achievement test, in favor of the experimental group. Additionally, the use of the sheltered instruction observation protocol (SIOP) model also had a high impact on the size of the achievement test by more than 0.14 as measured by squared Eta effect size. The use of the sheltered instruction observation protocol (SIOP) model was characterized by high effectiveness in developing mathematical achievement for students of the preparatory year in the experimental groups. The research also recommended the importance of training teachers on how to prepare and apply the sheltered instruction observation protocol (SIOP) model, paying attention to activities that combine content and language
Keywords: Preparatory Year; Sheltered Instruction Observation Protocol (SIOP); (SIOP); Achievement